Synkope – Eine praktische Abklärungsstrategie - Nemeth, Blanka; Weber, Elisabeth; Huber, Lars Christian (DMW - Deutsche Medizinische Wochenschrift, 2018)
Syncope is defined as a transient, self-limited loss of consciousness due to insufficient cerebral blood perfusion. In a clinical setting, syncopal events usually present a diagnostic dilemma due to its broad differential diagnosis ranging from banal to potentially harmful causes. In the absence of a working hypothesis, multiple tests are ordered that result in high costs but are of questionable diagnostic and therapeutic value. This article provides a practical overview and, based on international guidelines and selected studies, proposes a standardized approach to patients with syncope. Initial evaluation of these patients includes taking a careful medical history, physical examination and ECG. These tests result in an individual risk assessment that supports decision-making whether further analysis should be performed in an outpatient or inpatient setting. Additional tests including echocardiography, laboratory analysis, cardiac monitoring, CT-scans, are ordered according to prior evaluation. This article reviews the most common diagnostic tests, their indications and the clinical relevance for the evaluation of patients with syncopal events. Therapeutic options are not within the focus of this article.
Keywords: Synkope; standardisiertes Vorgehen; Erstbeurteilung; Risikostratifikation